Tensile capacity of self-piercing rivet connections in thin-walled steel structures. (May 2018) - Xie, Zhiqiang; Yan, Weiming; Yu, Cheng; Mu, Tingting; Song, Linlin
Abstract: The paper presents an experimental investigation on the tensile behavior and strength of self-piercing rivet (SPR) connections used in cold-formed thin-walled steel structures. The sheet thickness ratio, the sheet combination type, and the rivet length were analyzed for their effects on the tensile performance of SPR connections. The research also studied the feasibility of the existing calculation method of SPR connections and the other design methods of self-tapping screw connections for the SPRs investigated herein. Based on the test results and analyses, a new design method for the tensile capacity was proposed. The test results showed that the sheet thickness ratio, the sheet combination type, and the rivet length were the key factors controlling the failure mode and the tensile capacity of SPR connections. The proposed design method for the tensile capacity of SPR connections considers those primary factors as well as the different failure modes. Highlights: Pilot research on self-piercing rivet connections in cold-formed steel structures Extensive test matrix to address a large variation of connection configurations and failure modes Recommendation for appropriate details of self-piercing rivet connections for cold-formed steel structures is developed. Design method of tension strength for self-piercing rivet connections in cold-formed steel structures is proposed.